(untitled) (Ibrahim Medical College Journal, 2009)
This study was undertaken to estimate cost differentials between private and public hospitals for antimicrobial treatment of the admitted paediatiric patients who were suffering from pneumonia or diarrhoea - the two most common infectious paediatric problems in Bangladesh. The study was conducted between August 2002 and January 2003 in paediatric wards of two selected medical college hospitals-one public and the other private. The treatment charts of 107 admitted paediatric patients who received antimicrobial agent(s) for the treatment of pneumonia (88) or diarrhoea (19) were reviewed daily from the day of admission of the patients till their discharge from the hospitals. The total costs of antimicrobial agents per patient were based on the current market price of these agents. The average cost of antimicrobial course(s) per patient of pneumonia were for great in private hospital while that of diarrhoea was higher in public hospital. Ibrahim Med. Coll. J. 2008; 2(2): 61-64 Key Words: Antimicrobial therapy, cost differentials, pneumonia, diarrhoea. doi: 10.3329/imcj.v2i2.2940